Desarrollo de un plan estratégico para una fábrica de plásticos en el área de control de calidad de productos utilizando los indicadores de evaluación de gestión - Avilés Chacón, Liliana (2010)
The objective of the present study this guided to develop a strategic plan for the area of control of quality of products of the company Plásticos Ecuatorianos s.a. (PESA) using balanced indicators of administration evaluation and integrated in four perspectives (clients, shareholders, internal processes, intangible capital and society). The indicators of administration evaluation helped the efficiency, effectiveness and productivity of this area, allowing to prioritize activities and processes based on the necessity of execution of objectives to short, medium and long time, identifying opportunities of improvement and optimization in those works or processes that for their behavior and tendencies require of a reorientation or a reinforcement. With the study it is hoped to propose the use of new indicators and to integrate them in a Balanced Scorecard.